ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT REPORT LAG PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (Studi Empiris pada Perusahaan Subsektor Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2020) - Dessy Rachmawati; Suyatmin Waskito Adi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Along with the development of the times, activities that occur in Indonesia have progressed very rapidly, one of which is the progress of the capital market, this progress is marked by the number of companies registering themselves on the IDX and also many companies that have gone public. This study aims to determine how the effect of public accounting firm size, firm size, auditor turnover, profitability, solvency, and ownership structure on audit report delays using a quantitative approach and purposive sampling method. The results of this study indicate that the size of the public accounting firm and solvency have an effect on audit report lag, while firm size, auditor turnover, profitability, and ownership structure have no effect on audit report lag.